Application of Local Numerical Homogenization and hp-Adaptive FEM for Modeling of Heterogeneous Viscoelastic Materials - Marek KLIMCZAK; Witold CECOT (Engineering Transactions, 2015)
In this paper the application of local numerical homogenization and hp-adaptive FEM for modeling of non-periodic heterogeneous viscoelastic materials is presented. These two methods were combined and modified in order to provide a novel tool for reliable and efficient analyses of structures made of the above mentioned materials. Short descriptions of both numerical methods as well as our approach are provided. Several numerical examples are presented in order to validate the effectiveness of the proposed method.